Optimal timing of simethicone administration prior to upper endoscopy: A multicenter, single-blind, randomized controlled trial - Beaufort, I.N.; Verbeek, R.E.; Bosman, J.H.; Al-Toma, A.; Bogte, A.; Alvarez Herrero, L.; Weusten, B.L.A.M. (Endoscopy International Open, 2023)
Background and study aims Simethicone is useful as premedication for upper endoscopy because of its antifoaming effects. We aimed to evaluate the effect of timing of simethicone administration on mucosal visibility.Patients and methods In this multicenter, randomized, endoscopist-blinded study, patients scheduled for upper endoscopy were randomized to receive 40 mg simethicone at the following time points prior to the procedure: 20 to 30 minutes (early group), 0 to 10 minutes (late group) or 20 mg simethicone at both time points (split-dose group). Images were taken from nine predefined locations in the esophagus, stomach, and duodenum before endoscopic flushing. Each image was scored on mucosal visibility by three independent endoscopists on a 4-point scale (lower scores indicating better visibility), with adequate mucosal visibility defined as a score ≤ 2. Primary outcome was the percentage of patients with adequate total mucosal visibility (TMV), reached if all median subscores for each location were ≤ 2.Results A total of 386 patients were included (early group: 132; late group: 128; split-dose group: 126). Percentages of adequate TMV were 55%, 42%, and 61% in the early, late, and split-dose group, respectively (P < 0.01). Adequate TMV was significantly higher in the split-dose group compared to the late group (P < 0.01), but not compared to the early group (P = 0.29). Differences between groups were largest in the stomach, where percentages of adequate mucosal visibility were higher in the early (68% vs 53%, P = 0.03) and split-dose group (69% vs 53%, P = 0.02) compared to the late group.Conclusions Mucosal visibility can be optimized with early simethicone administration, either as a single administration or in a split-dose regimen.
Keywords: Precancerous conditions & cancerous lesions (displasia and cancer) stomach; Barrett's and adenocarcinoma; Preparation, quality and logistical aspects; Quality management; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE)